Clinical Variation of Plasmodium falciparum eba-175, ama-1, and msp-3 Genotypes in Young Children Living in a Seasonally High Malaria Transmission Setting in Burkina Faso. (8th November 2015) - Soulama, Issiaka; Sermé, Samuel S.; Bougouma, Edith C.; Diarra, Amidou; Tiono, Alfred B.; Ouedraogo, Alphonse; Konate, Amadou T.; Nebie, Issa; Sirima, Sodiomon B.
Abstract : The association between P. falciparum eba-175, ama-1, and msp-3 polymorphism in the pathogenicity of malaria disease was investigated. We therefore compared the prevalence of different alleles between symptomatic and asymptomatic malarial children under five years of age living in Burkina Faso. Blood filter papers were collected during the 2008 malaria transmission season from 228 symptomatic and 199 asymptomatic children under five years of age. All patients were living in the rural area of Saponé at about 50 km from Ouagadougou, the capital city of Burkina Faso. P. falciparum parasite DNA was extracted using QIAGEN kits and the alleles diversity was assessed by a nested PCR. PCR products were then digested by restriction enzymes based on already described polymorphic regions of the eba-175, ama-1, and msp-3 genes. The individual alleles eba-175_FCR3 and msp-3_K1 frequencies were statistically higher (p < 0.0001 ) in the asymptomatic group compared to the symptomatic ones. No statistically significant difference was noted in the prevalence of ama-1 -3D7, ama-1 -K1, and ama-1 -HB3 genotypes between the two groups (p > 0.05 ). The comparative analysis of P. falciparum genotypes indicated that the polymorphism in eba - 175 and msp-3 genotypes varied between asymptomatic and symptomatic clinical groups and may contribute to the pathogenesis of malaria.